PENGARUH DISIPLIN KERJA, MOTIVASI KERJA, ETOS KERJA DAN LINGKUNGAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN: STUDI PADA PT. TJIWI KIMIA - Christianadi, Januar Ika; Sopiah, Sopiah; Zagladi, Arief Noviarakhman (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2024)
This study aims to analyze the impact of work discipline, work motivation, work ethic, and work environment on employee productivity at PT. Tjiwi Kimia. In the competitive era of globalization, employee productivity has become a crucial factor for a company's success, particularly in the manufacturing sector. The research uses a quantitative approach with an explanatory method and survey through questionnaires distributed to a sample of employees using stratified random sampling technique. The results of the analysis show that work discipline, work motivation, work ethic, and work environment significantly affect employee productivity, both individually and simultaneously. Work discipline and motivation were found to have the greatest contribution to improving productivity. The study concludes that managing these factors is essential for the company to enhance efficiency and competitiveness. Therefore, it is recommended that PT. Tjiwi Kimia improve its programs on discipline, motivation, and creating a conducive work environment to achieve optimal productivity.